A PMP / Bio-PA nanofiber filter material with electret effect and preparation method thereof

Through electrospinning technology, PMP and Bio-PA are blended, which solves the problem of attenuation of the electret effect of electrospinning filter materials in the prior art, and realizes high-efficiency and low-resistance nanofiber filter materials, meeting the protection requirements of N95 masks.

CN115569442BActive Publication Date: 2025-03-04GUIZHOU CHIEN YEH PLASTIC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211333883.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-28
Publication Date
2025-03-04
Estimated Expiration
2042-10-28

AI Technical Summary

Technical Problem

It is difficult for existing electrospinning filter materials to achieve high electret performance without adding nanoparticles, and the electret effect is prone to attenuation, which cannot meet the effective protection requirements of N95 masks for PM0.3.

Method used

The PMP and Bio-PA polymers were blended in different proportions by electrospinning technology, and the electroporating behaviors between them were complementary to obtain nanofiber filter materials with excellent electret properties.

Benefits of technology

Nanofiber filter materials with high porosity, low resistance pressure drop and high filtration efficiency can effectively filter PM0.3 particles, meet the protection requirements of N95 masks, and avoid the potential harm of nanoparticles falling off to human health.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a PMP / Bio-PA nanofiber filter material with an electret effect and a preparation method thereof, which is obtained by electrostatic spinning of PMP and Bio-PA; wherein the mass ratio of the PMP to the Bio-PA is 5-75:25-95. The present invention utilizes the complementarity of the electric polarization behavior between the two polymers PMP and Bio-PA to obtain an electrostatically spun nanofiber with excellent electret performance, selects PMP as the matrix material for fiber construction, and Bio-PA as an electret enhancer, and Bio-PA is evenly distributed in the matrix PMP fiber, thereby overcoming the bottleneck problem that the existing nanoparticle-type electret enhancer is easy to agglomerate and fall off, which brings secondary harm to human health and cannot be used in the field of medical protection, and at the same time avoids the problem that the electret melt-blown fiber is complicated in process and the electret effect is easy to decay.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrostatic spinning nanofiber filter materials, and specifically relates to a PMP / Bio-PA nanofiber filter material with an electret effect and a preparation method thereof. Background Art

[0002] The Corona Virus Disease 2019 (COVID-19) has caused a sharp decline in the global economy. One of the main ways the virus spreads is through droplets, so wearing a mask has become a basic measure to reduce the risk of infection and control the spread of the epidemic. During the epidemic, N95 protective masks suitable for medical staff need to meet the filtration efficiency of >95% for 300nm aerosol (PM0.3) particles to prevent the virus from entering the human body in the form of aerosols.

[0003] As the core material of masks, the main component of the meltblown non-woven fabrics currently on the market is polypropylene fibers with coarse diameters and large pore sizes. It is difficult to effectively filter fine aerosol particles by simply relying on physical interception. Therefore, they are often treated with electrostatic charging to improve the filtration efficiency in order to meet the higher requirements of N95 masks for protective performance. However, the electret effect of electret meltblown fibers is easy to decay because the two steps of fiber forming and electret application are independent of each other. Once the electret effect is lost, the filtration efficiency generated by physical interception cannot meet the effective protection of PM0.3. Electrospinning technology is a special fiber in-situ electret technology that can realize the one-step preparation of electret fibers. It can also simultaneously regulate the electrostatic electret effect and morphological structural characteristics of the fibers by changing the properties of the precursor polymer solution. The electrospun electret air filter materials reported so far have a common feature, which is to increase the electret effect of electrospun fibers by introducing nanoparticles (such as titanium dioxide, silicon dioxide, boehmite, etc.). However, the inherent agglomeration behavior of nanoparticles makes it difficult for the particles to be evenly distributed in the fibers, and thus they can easily fall off from the fiber matrix, causing secondary harm to human health when the fibers are used as personal protective materials (such as masks). Therefore, how to prepare electrospun fiber filter materials with high electret performance without adding nanoparticles has become one of the problems that need to be solved urgently.

[0004] The dielectric constant of poly-4-methyl-1-pentene (PMP) is 2.06, which is a weakly polar polymer, and its electret performance mainly comes from space charge. The dielectric constant of Bio-PA is between 4.0-5.5, which is a strongly polar polymer, and its electret performance mainly comes from dipole charge. This patent uses the complementarity of the polarization behavior between the two polymers to obtain electrospun nanofibers with excellent electret performance. By blending PMP and Bio-PA in different proportions, an electrospun electret fiber membrane with synergistic enhancement of space charge and dipole charge is obtained. The fiber membrane has a high porosity and exhibits high-efficiency and low-resistance air filtration performance, which can completely replace traditional processing methods. Moreover, PMP has the lowest density among thermoplastic materials (0.83g / cm 3 ), relatively speaking, the mass per unit volume is much smaller, so it meets the lightweight requirements of personal care and medical products; PMP has a stable CC bond, good chemical resistance and drug resistance, complies with the regulations of the U.S. Food and Drug Administration (FDA) and EU regulations, and has excellent hygiene and safety. Bio-based polyamide (Bio-PA) material refers to the raw materials required for the production of polyamide (generally dibasic acids, diamines or cyclic lactams) using renewable biomass resources such as glucose, cellulose, and vegetable oils (including castor oil, oleic acid and linoleic acid, etc.), obtained through bioengineering methods. Compared with the current world's more than 99% of PA product raw materials come from non-renewable resources-petroleum, bio-based polyamide has the characteristics of green, environmentally friendly, and renewable raw materials. The CO2 generated during the production process can be offset by the CO2 consumed by plants during their growth. Therefore, from the perspective of the entire life cycle, its carbon emissions are zero, which is in line with the dual carbon goals of carbon peak and carbon neutrality advocated in the current environment.

[0005] Chinese patent CN112281250A discloses an antibacterial melt-blown polyamide composite material, which is mainly composed of short-chain polyamide resin, long-chain polyamide resin, electret agent, and loaded silver ion antibacterial agent. Among them, by adopting the compounding of two polyamide resins, the melt-blown polyamide cloth with short carbon chain as the main component is mixed with long-chain polyamide resin, which improves the dispersibility of the loaded silver ion antibacterial agent, thereby alleviating the defect that the addition of the loaded silver ion antibacterial agent will cause the air permeability of the melt-blown polyamide cloth to deteriorate, and can reduce the water absorption of the material, and ensure the charge stability of the melt-blown product during long-term storage and practical use. However, the loaded silver ion antibacterial agent used in this patent will inevitably agglomerate and then fall off in the polyamide fiber, so that when the polyamide fiber is used as a mask, it will bring secondary harm to human health. The patent adopts the melt-blown method to prepare the polyamide fiber, which makes the electret effect easy to decay, and the filtration efficiency is difficult to meet the requirements of PM 0.3 effective protection.

[0006] Chinese patent CN113710344A discloses a filter medium comprising a polyamide nanofiber layer. The polyamide may have a relative viscosity of 2 to 200. The polyamide nanofiber layer may have a melting point of 225°C or higher. The nanofiber may have an average fiber diameter of less than 1000 nanometers (1 micron). However, the patent does not involve polyamide and polyolefins such as poly-4-methyl-1-pentene (PMP).

[0007] Chinese patents CN113398773A, CN114474915A, CN114749032A and CN114749036A all involve the preparation of PMP into nano hollow molds for use in blood oxygenation membranes in ECMO systems. There are no reports on the electrospinning of PMP into nano fiber membranes for use in protective masks. Summary of the invention

[0008] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0009] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0010] One of the purposes of the present invention is to provide a PMP / Bio-PA nanofiber filter material with electret effect, and to obtain electrospun nanofibers with excellent electret properties by utilizing the complementarity of the electrical polarization behaviors between the two polymers PMP and Bio-PA.

[0011] In order to solve the above technical problems, the present invention provides the following technical solutions: a PMP / Bio-PA nanofiber filter material with electret effect, which is obtained by electrostatic spinning of PMP and Bio-PA;

[0012] Wherein, the mass ratio of the PMP to the Bio-PA is 5-75:25-95;

[0013] The PMP / Bio-PA nanofiber filter material with electret effect has the following characteristics:

[0014] (i) Porosity ≥ 99%;

[0015] (ii) pore size 0.2~4.5μm;

[0016] (iii) Filtration efficiency ≥ 99.947%;

[0017] (iv) Resistance pressure drop ≤ 33 Pa;

[0018] (v) Surface electrostatic potential 100~9000V;

[0019] (vi) The fiber diameter is 50~900nm.

[0020] As a preferred solution of the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, the PMP is unbranched isotactic poly-4-methyl-1-pentene.

[0021] As a preferred embodiment of the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, wherein: the polymer monomer raw material of the Bio-PA is entirely or partially derived from one or more combinations of castor oil, glucose, starch, grease or vegetable oil;

[0022] The polymerized monomer acid of the Bio-PA is one or a combination of amino acids or dibasic acids having 2 to 14 carbon atoms.

[0023] The polymerized monomer amine of the Bio-PA is one or a combination of multiple diamines having 2 to 14 carbon atoms.

[0024] As a preferred embodiment of the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, the polymerized monomer acid of Bio-PA includes one or more of 11-amino acid, sebacic acid, terephthalic acid, dodecanedioic acid, adipic acid, caprolactam, succinic acid, γ-aminobutyric acid, and azelaic acid.

[0025] As a preferred embodiment of the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, the polymerized monomer amine of Bio-PA includes one or a combination of multiple of decanediamine, hexamethylenediamine, butanediamine and pentamethylenediamine.

[0026] As a preferred embodiment of the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, the Bio-PA is one or a combination of more of PA11, PA1010, PA410, PA610, PA10T, PA1012, PA66, PA6, PA46, PA4, PA56, and PA69.

[0027] Another object of the present invention is to provide a method for preparing the PMP / Bio-PA nanofiber filter material with electret effect as described in any of the above items, comprising electrospinning a mixed spinning solution containing PMP and Bio-PA in a high humidity environment.

[0028] As a preferred embodiment of the method for preparing the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, the mixed spinning solution containing PMP and Bio-PA is obtained by dissolving Bio-PA and PMP in corresponding solvents respectively and stirring and mixing;

[0029] The solvent is one or a combination of formic acid, cresol, methanol, toluene, glacial acetic acid, ethanol, acetonitrile, dichloromethane, 1,2-dichloroethylene, acetone, propanol, isopropanol, chloroform, trichloroethylene, butanol, isobutanol, chloroform, cyclohexane, tetrachloroethylene, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methyl-2-pyrrolidone.

[0030] As a preferred embodiment of the method for preparing the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, the concentration of the mixed spinning solution is 0.5-55wt%;

[0031] The mixing and stirring has a stirring time of 2 to 48 hours, a stirring speed of 100 to 1000 rpm, and a stirring temperature of 25 to 95°C.

[0032] As a preferred embodiment of the method for preparing the PMP / Bio-PA nanofiber filter material with electret effect of the present invention, the electrospinning is performed with a voltage of 10-150 kV, a perfusion speed of 0.1-15 mL / h, a receiving distance of 5-65 cm, an ambient temperature of 0-40° C., and an ambient relative humidity of 55-95%.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention utilizes the complementarity of the electric polarization behavior between two polymers, PMP and Bio-PA, to obtain electrostatically spun nanofibers with excellent electret properties, selects PMP as a matrix material for fiber construction, and Bio-PA as an electret reinforcing agent. Bio-PA is evenly distributed in the matrix PMP fiber, thereby overcoming the bottleneck problem that the existing nanoparticle-type electret reinforcing agent is easy to agglomerate and fall off, causing secondary harm to human health and thus cannot be used in the field of medical protection, and at the same time avoids the problem that the electret melt-blown fiber has a complex process and the electret effect is easy to attenuate. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0038] Unless otherwise specified, the raw materials used in the examples were purchased commercially. Example 1

[0039] (1) PMP was placed in N,N-dimethylformamide and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 70°C to obtain spinning solution A;

[0040] (2) PA11 was placed in formic acid and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 70°C to obtain spinning solution B;

[0041] (3) After spinning solution A and spinning solution B are mixed, the stirring is continued for 2 hours, the stirring speed is 400 rpm, and the stirring temperature is 70°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA11 is maintained at 7:1; and the concentration of the mixed spinning solution is maintained at 7wt%;

[0042] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 75%, starting the electrospinning process, and receiving the obtained PMP / PA11 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 20 kV, receiving distance 5 cm, infusion speed 0.4 mL / h, spinning temperature 23 °C.

[0043] The following performance tests were performed on the finally prepared PMP / PA11 nanofiber filter material with electret effect.

[0044] (1) Fiber diameter: The surface morphology of the nanofiber filter material was observed using a scanning electron microscope (JSM-6490LV, Japan Electronics). The obtained SEM image was imported into the Image Pro Plu analysis software, and 200 fibers were randomly selected to calculate the average fiber diameter. The average fiber diameter was measured to be 190 nm.

[0045] (2) Pore size: The pore size of the prepared nanofiber filter material was tested using a PSM-65 pore size analyzer produced by TOPAS in Germany. The average pore size was measured to be 0.8 μm.

[0046] (3) Porosity: The porosity (p) of the material can be obtained by the following formula p = (1-m⁄ρSH) × 100%, where m, S and H represent the gram weight, area and thickness of the nanofiber assembly, and ρ is the density of PVDF. The gram weight was measured by an analytical balance (AXS205, Mettler Toledo), the area was measured by a ruler, and the thickness was measured on a Labthink high-precision thickness gauge (CHYC2). The porosity of the material was measured to be 99.2%.

[0047] (4) Surface electrostatic potential: The electret performance of the material is tested using a non-contact electrostatic instrument (TREK520-1-CE USA). During the test, the sample is suspended horizontally at a certain height. When the sensor probe of the instrument moves 2 cm above the sample, the surface potential of the material is automatically displayed in real time on the display panel of the instrument. The measured surface electrostatic potential of the material is 6310V.

[0048] (5) Filtration efficiency and resistance pressure drop: The filtration performance of the electret nanofiber material was tested according to GB 19083-2010; the data were measured by an automatic filter tester (AFC-131, TOPAS, Germany) with a test area of ​​100 cm 2 The filtration efficiency value given is the filtration efficiency for the most penetrating particle size (MPPS, 0.3μm). The filtration efficiency of the material was measured to be 99.951% and the resistance pressure drop was 30Pa. Example 2

[0049] (1) PMP was placed in acetone and stirred for 12 h at a stirring speed of 300 rpm and a stirring temperature of 80°C to obtain spinning solution A;

[0050] (2) PA410 was placed in formic acid and mixed and stirred for 12 h at a stirring speed of 300 rpm and a stirring temperature of 80 °C to obtain spinning solution B;

[0051] (3) After spinning solution A and spinning solution B are mixed, the stirring is continued for 2 h, the stirring speed is 200 rpm, and the stirring temperature is 80°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA410 is maintained at 5:2; at the same time, the concentration of the mixed spinning solution is maintained at 10 wt%;

[0052] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 85%, starting the electrospinning process, and receiving the obtained PMP / PA410 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 30 kV, receiving distance 7 cm, infusion speed 0.7 mL / h, spinning temperature 20 °C.

[0053] The performance of the PMP / PA410 nanofiber filter material with electret effect finally obtained in Example 2 was tested using the testing method in Example 1. The test results were: porosity 99.2%, pore size 0.7 μm, filtration efficiency 99.972%, resistance pressure drop 33 Pa, surface electrostatic potential 7840 V, and fiber diameter 294 nm. Example 3

[0054] (1) PMP was placed in N,N-dimethylacetamide and mixed and stirred for 15 h at a stirring speed of 350 rpm and a stirring temperature of 60°C to obtain spinning solution A;

[0055] (2) PA610 was placed in formic acid and mixed and stirred for 15 h at a stirring speed of 350 rpm and a stirring temperature of 60 °C to obtain spinning solution B;

[0056] (3) Spinning solution A and spinning solution B were mixed and then continued to be stirred for 2 h at a stirring speed of 350 rpm and a stirring temperature of 60°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA610 was maintained at 5:3; and the concentration of the mixed spinning solution was maintained at 12 wt%;

[0057] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 95%, starting the electrospinning process, and receiving the obtained PMP / PA610 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 40 kV, receiving distance 9 cm, infusion speed 0.9 mL / h, spinning temperature 23 °C.

[0058] The performance of the PMP / PA610 nanofiber filter material with electret effect finally obtained in Example 3 was tested using the testing method in Example 1. The test results were: porosity 99.3%, pore size 1.1 μm, filtration efficiency 99.948%, resistance pressure drop 26 Pa, surface electrostatic potential 8970 V, and fiber diameter 170 nm. Example 4

[0059] (1) PMP was placed in cyclohexane and mixed and stirred for 20 h at a stirring speed of 280 rpm and a stirring temperature of 65 °C to obtain spinning solution A;

[0060] (2) PA1012 was placed in formic acid and mixed and stirred for 20 h at a stirring speed of 280 rpm and a stirring temperature of 55 °C to obtain spinning solution B;

[0061] (3) Spinning solution A and spinning solution B were mixed and then continued to be stirred for 2 h, at a stirring speed of 280 rpm and at a stirring temperature of 65°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA1012 was maintained at 7:2; and the concentration of the mixed spinning solution was maintained at 12 wt%;

[0062] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 90%, starting the electrospinning process, and receiving the obtained PMP / PA1012 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 35 kV, receiving distance 15 cm, infusion speed 2.2 mL / h, spinning temperature 25 °C.

[0063] The performance of the PMP / PA1012 nanofiber filter material with electret effect finally obtained in Example 4 was tested using the testing method in Example 1. The test results were: porosity 99.2%, pore size 1.3 μm, filtration efficiency 99.977%, resistance pressure drop 21 Pa, surface electrostatic potential 6750 V, and fiber diameter 153 nm. Example 5

[0064] (1) PMP was placed in N,N-dimethylformamide and mixed and stirred for 8 h at a stirring speed of 500 rpm and a stirring temperature of 85°C to obtain spinning solution A;

[0065] (2) PA56 was placed in formic acid and mixed and stirred for 8 h at a stirring speed of 500 rpm and a stirring temperature of 85 °C to obtain spinning solution B;

[0066] (3) After spinning solution A and spinning solution B are mixed, the stirring is continued for 2 hours, the stirring speed is 500 rpm, and the stirring temperature is 85°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA1012 is maintained at 8:2; at the same time, the concentration of the mixed spinning solution is maintained at 10wt%;

[0067] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 85%, starting the electrospinning process, and receiving the obtained PMP / PA56 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 50 kV, receiving distance 12 cm, infusion speed 2.8 mL / h, spinning temperature 20°C.

[0068] The performance of the PMP / PA56 nanofiber filter material with electret effect finally obtained in Example 5 was tested using the testing method in Example 1. The test results were: porosity 99.5%, pore size 2.5 μm, filtration efficiency 99.973%, resistance pressure drop 15 Pa, surface electrostatic potential 6470 V, and fiber diameter 120 nm. Example 6

[0069] (1) PMP was placed in N,N-dimethylacetamide and mixed and stirred for 24 h at a stirring speed of 550 rpm and a stirring temperature of 85°C to obtain spinning solution A;

[0070] (2) PA10T was placed in formic acid and mixed and stirred for 24 h at a stirring speed of 550 rpm and a stirring temperature of 85 °C to obtain spinning solution B;

[0071] (3) After spinning solution A and spinning solution B are mixed, stirring is continued for 2 h at a stirring speed of 550 rpm and a stirring temperature of 85 °C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA610 is maintained at 9:5; at the same time, the concentration of the mixed spinning solution is maintained at 20 wt%.

[0072] (4) placing the mixed spinning solution obtained in step (3) in a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 75%, starting the electrospinning process, and receiving the obtained PMP / PA10T nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 75 kV, receiving distance 20 cm, infusion speed 8 mL / h, spinning temperature 35 °C.

[0073] The performance of the PMP / PA10T nanofiber filter material with electret effect finally obtained in Example 6 was tested using the testing method in Example 1. The test results were: porosity 99.7%, pore size 1.5 μm, filtration efficiency 99.976%, resistance pressure drop 19 Pa, surface electrostatic potential 6590 V, and fiber diameter 140 nm. Example 7

[0074] (1) PMP was placed in N,N-dimethylformamide and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain spinning solution A;

[0075] (2) PA1010 was placed in formic acid and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 80 °C to obtain spinning solution B;

[0076] (3) After spinning solution A and spinning solution B are mixed, the stirring is continued for 2 hours at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA1010 is maintained at 9:1; and the concentration of the mixed spinning solution is maintained at 15wt%;

[0077] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 95%, starting the electrospinning process, and receiving the obtained PMP / PA1010 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 40 kV, receiving distance 10 cm, infusion speed 1.0 mL / h, spinning temperature 23 °C.

[0078] The performance of the PMP / PA1010 nanofiber filter material with electret effect finally obtained in Example 7 was tested using the testing method in Example 1. The test results were: porosity 99.8%, pore size 0.9 μm, filtration efficiency 99.969%, resistance pressure drop 23 Pa, surface electrostatic potential 8050 V, and fiber diameter 166 nm. Comparative Example 1

[0079] (1) PMP was placed in N,N-dimethylformamide and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain spinning solution A;

[0080] (2) PA1010 was placed in formic acid and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain spinning solution B;

[0081] (3) After spinning solution A and spinning solution B are mixed, the stirring is continued for 2 hours at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA1010 is maintained at 1:9; and the concentration of the mixed spinning solution is maintained at 15wt%;

[0082] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 95%, starting the electrospinning process, and receiving the obtained PMP / PA1010 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 40 kV, receiving distance 10 cm, infusion speed 1.0 mL / h, spinning temperature 23 °C.

[0083] The difference between Comparative Example 1 and Example 7 is that the mass ratio of PMP and PA1010 in Comparative Example 1 is adjusted from 9:1 to 1:9, and the other process conditions remain unchanged. Comparative Example 1 ultimately fails to produce a PMP / Bio-PA nanofiber filter material with an electret effect.

[0084] The performance of the filter material finally obtained in Comparative Example 1 was tested using the testing method in Example 1. The material had a porosity of 56.7%, a pore size of 2.5 μm, a filtration efficiency of 63.747%, a resistance pressure drop of 113 Pa, a surface electrostatic potential of 1350 V, and a fiber diameter of 753 nm.

[0085] It can be seen that when the Bio-PA content is too high to become the matrix material for fiber construction, and PMP is a weakly polar polymer, it cannot play the role of a charging enhancer, resulting in the failure of electrospinning and an unsatisfactory charging effect, which cannot meet the requirements of medical staff wearing N95 protective masks. Comparative Example 2

[0086] (1) PMP was placed in N,N-dimethylformamide and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain spinning solution A;

[0087] (2) PA1010 was placed in formic acid and mixed and stirred for 8 h at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain spinning solution B;

[0088] (3) After spinning solution A and spinning solution B are mixed, the stirring is continued for 2 hours at a stirring speed of 400 rpm and a stirring temperature of 80°C to obtain a mixed spinning solution; during the mixing process, the mass ratio of PMP to PA1010 is maintained at 9:1; and the concentration of the mixed spinning solution is maintained at 15wt%;

[0089] (4) placing the mixed spinning solution obtained in step (3) into a liquid supply device, adjusting the electrospinning process parameters, connecting a high voltage power supply, adjusting the relative humidity of the spinning environment to 40%, starting the electrospinning process, and receiving the obtained PMP / PA1010 nanofibers with electret effect through a collecting device; wherein the electrospinning process parameters are: voltage 40 kV, receiving distance 10 cm, infusion speed 1.0 mL / h, spinning temperature 23 °C.

[0090] The difference between Comparative Example 2 and Example 7 is that in Comparative Example 2, the relative humidity of the spinning environment is adjusted from 95% to 40%, and the mass ratio of PMP and PA1010, the type of solvent and other process conditions remain unchanged.

[0091] The fiber obtained in Comparative Example 2 presents a beaded structure. The performance of the filter material finally obtained in Comparative Example 2 was tested by the testing method in Example 1. The material obtained by the test had a porosity of 78.5%, a pore size of 3.1 μm, a filtration efficiency of 59.975%, a resistance pressure drop of 126 Pa, a surface electrostatic potential of 4870 V, and a fiber diameter of 755 nm, which cannot meet the requirements of medical staff wearing N95 protective masks.

[0092] The present invention utilizes the complementarity of the electric polarization behavior between two polymers, PMP and Bio-PA, to obtain electrostatic spinning nanofibers with excellent electret performance, selects PMP as the matrix material for fiber construction, and Bio-PA as the electret reinforcing agent. Bio-PA is evenly distributed in the matrix PMP fiber, which overcomes the bottleneck problem that the existing nanoparticle type electret reinforcing agent is easy to agglomerate and fall off, which brings secondary harm to human health and cannot be used in the field of medical protection, and at the same time avoids the problem that the electret melt-blown fiber is complicated in process and the electret effect is easy to decay. The prepared PMP / Bio-PA nanofiber filter material with electret effect has a porosity of ≥99%, a pore size of 0.2-4.5 μm, a filtration efficiency of ≧99.947%, a resistance pressure drop of ≦33 Pa, a surface electrostatic potential of 100-9000 V, and a fiber diameter of 50-900 nm.

[0093] The preparation method of the present invention is simple and easy and can be mass-produced. Compared with current commercial filter materials and reported electrospinning filter materials, when having the same filtration level, the PMP / Bio-PA nanofiber filter material with electret effect has a more prominent low pressure resistance advantage in practical applications, and the obtained product meets the requirements of medical staff wearing N95 protective masks.

[0094] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A PMP / Bio-PA nanofiber filter material with electret effect, characterized in that: It was obtained by electrospinning PMP and Bio-PA; The mass of the PMP accounts for 62.5-90% of the total mass of the PMP and Bio-PA; The PMP / Bio-PA nanofiber filter material with electret effect has the following characteristics: (i) Porosity ≥ 99%; (ii) pore size 0.2~4.5μm; (iii) Filtration efficiency ≥ 99.947%; (iv) Resistance pressure drop ≤ 33 Pa; (v) Surface electrostatic potential 100~9000V; (vi) The fiber diameter is 50~900nm.

2. The PMP / Bio-PA nanofiber filter material with electret effect as claimed in claim 1, characterized in that: The PMP is unbranched isotactic poly-4-methyl-1-pentene.

3. The PMP / Bio-PA nanofiber filter material with electret effect as claimed in claim 1 or 2, characterized in that: The polymerizable monomer raw materials of the Bio-PA are wholly or partially derived from castor oil, glucose, starch, grease or vegetable oil or a combination of one or more thereof; The polymerized monomer acid of the Bio-PA is one or a combination of amino acids or dibasic acids having 2 to 14 carbon atoms; The polymerized monomer amine of the Bio-PA is one or a combination of multiple diamines having 2 to 14 carbon atoms.

4. The PMP / Bio-PA nanofiber filter material with electret effect as claimed in claim 3, characterized in that: The polymerizable monomer acid of the Bio-PA includes one or a combination of 11-amino acid, sebacic acid, terephthalic acid, dodecanedioic acid, adipic acid, caprolactam, succinic acid, γ-aminobutyric acid, and azelaic acid.

5. The PMP / Bio-PA nanofiber filter material with electret effect as claimed in claim 3, characterized in that: The polymerized monomer amine of the Bio-PA includes one or a combination of multiple of decanediamine, hexamethylenediamine, butanediamine and pentamethylenediamine.

6. The PMP / Bio-PA nanofiber filter material with electret effect as claimed in claim 4 or 5, characterized in that: The Bio-PA is one or a combination of more of PA11, PA1010, PA410, PA610, PA10T, PA1012, PA66, PA6, PA46, PA4, PA56, and PA69.

7. The method for preparing the PMP / Bio-PA nanofiber filter material with electret effect according to any one of claims 1 to 6, characterized in that: The method comprises electrospinning a mixed spinning solution containing PMP and Bio-PA in a high humidity environment, wherein the relative humidity of the environment is 55-95%.

8. The method for preparing the PMP / Bio-PA nanofiber filter material with electret effect as claimed in claim 7, characterized in that: The mixed spinning solution containing PMP and Bio-PA is obtained by dissolving Bio-PA and PMP in corresponding solvents respectively and stirring and mixing; The solvent is one or a combination of formic acid, cresol, methanol, toluene, glacial acetic acid, ethanol, acetonitrile, dichloromethane, 1,2-dichloroethylene, acetone, propanol, isopropanol, chloroform, trichloroethylene, butanol, isobutanol, chloroform, cyclohexane, tetrachloroethylene, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methyl-2-pyrrolidone.

9. The method for preparing the PMP / Bio-PA nanofiber filter material with electret effect as claimed in claim 8, characterized in that: The concentration of the mixed spinning solution is 0.5-55wt%; The stirring time is 2 to 48 hours, the stirring speed is 100 to 1000 rpm, and the stirring temperature is 25 to 95°C.

10. The method for preparing the PMP / Bio-PA nanofiber filter material with electret effect according to claim 9, characterized in that: The electrospinning is performed at a voltage of 10-150 kV, a perfusion speed of 0.1-15 mL / h, a receiving distance of 5-65 cm, and an ambient temperature of 0-40° C.

Citation Information

Patent Citations

  • Antibacterial melt-blown polyamide composite material as well as preparation method and application thereof

    CN112281250A

  • Poly (4-methyl-1-pentene) hollow fiber alloy membrane as well as preparation method and application thereof

    CN113398773A

  • Filter media comprising polyamide NANO fiber layer

    CN113710344A

  • Composite film as well as preparation method and packaging structure thereof

    CN114474915A

  • PMP hollow fiber membrane as well as preparation method and application thereof

    CN114749032A